2002
DOI: 10.1590/s0074-02762002000700007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological aspects of human parvovirus B19 infection in an urban area in Brazil (Niterói city area, State of Rio de Janeiro, Brazil)

Abstract: This study was designed to analyse the clinical and epidemiological data from human parvovirus B19 cases in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
1
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 29 publications
7
17
1
8
Order By: Relevance
“…The detection of 27 positive sera for specific IgM in the states of Rio de Janeiro and Espírito Santo was reported between 1992 and 1994 (Cubel et al 1996b). In Niteroi, from 1994 to 1999, IgM for parvovirus B19 was identified in 31.8% of the sera (105) by Oliveira et al (2002a). Positivity of 39.8% for anti-B19 IgM had already been shown by Cassinotti et al (1993).…”
Section: Discussionmentioning
confidence: 99%
“…The detection of 27 positive sera for specific IgM in the states of Rio de Janeiro and Espírito Santo was reported between 1992 and 1994 (Cubel et al 1996b). In Niteroi, from 1994 to 1999, IgM for parvovirus B19 was identified in 31.8% of the sera (105) by Oliveira et al (2002a). Positivity of 39.8% for anti-B19 IgM had already been shown by Cassinotti et al (1993).…”
Section: Discussionmentioning
confidence: 99%
“…The mostly asymptomatic nature of B19V infection in pregnancy, its absence from both antenatal and occupational screening, and the lack of a requirement for notification impede both professional vigilance and proper recording of its role in fetal loss. Major B19V outbreaks are described as running in a 4-6 year cycle (Oliveira et al, 2002;Nicolay & Cotter, 2009), but increasing awareness and testing of pregnant women in relation to slapped cheek syndrome has resulted in more focused testing in this patient sector and a trend to recognition of more frequent cycles of transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The seasonal profile of B19 activity in Niterói area was described by Oliveira et al (2002). Studying patients with exanthematic diseases, these authors found distinct peaks of B19 activity during a six year observation period, suggesting that the disease appears to cycle in approximately four or five years.…”
Section: Discussionmentioning
confidence: 98%
“…The study was done in two different years (1998 and 1999), the second of them corresponding to a season of high viral activity in the community (Oliveira et al 2002). The samples were obtained after informed consent from donors from the blood bank of Hospital Universitário Antônio Pedro (HUAP), Niterói, state of Rio de Janeiro, Brazil, and from Instituto Nacional de Câncer (Inca), Rio de Janeiro, state of Rio de Janeiro, Brazil.…”
Section: Methodsmentioning
confidence: 99%